Edukasi Mitigasi Banjir dan Dampaknya terhadap Stabilitas Ekonomi Masyarakat di Wilayah Tapanuli Tengah dan Aceh - Theresia Mastiur Ningsih Siagian; Edison Parulian; Julfizar Julfizar; Permai Yudi; Nickytha Linch De Hans Lumban Gaol (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Flooding is a frequent disaster in the regions of Central Tapanuli and Aceh, and has a significant impact on the economic stability of local communities. The low level of public understanding regarding flood mitigation and the resulting economic impacts is a major issue. This Community Service activity aims to provide education on flood mitigation and raise public awareness of its impact on the local economy. The methods used include outreach, training sessions, group discussions, and community-based mentoring. The target groups for the activity are affected communities, small business owners, and village officials. The results of the activity indicate an increase in the community’s understanding of flood risks, simple mitigation measures, and strategies to maintain economic stability, such as business diversification and financial management. Consequently, this programme contributes to strengthening the community’s resilience to flood disasters and supports the sustainability of the local economy in a more adaptive and resilient manner.